Overview of open source augmented reality toolkit - Mohamad Said, Mohd. Nihra Haruzuan (Persatuan Teknologi Pendidikan Malaysia, 2007)
Augmented reality or also known as AR is not a new technology. The technology has existed for almost 40 years ago after Ivan Sutherland introduced the first virtual reality (VR) application. At that time, works and research were mainly concerned to establish the hardware aspects of the technology. The head-mounted display (HMD) or some might called head-worn display is the result of augmented reality research and also one of the fundamental equipment for accessing the technology. As time goes by, the augmented reality technology has begin to mature to a point where the hardware cost and capabilities have collided to deliver a more feasible AR thus enable the rapid development of AR applications in many fields including education. To create a non-commercial AR application specifically for education, the ARToolkit can be taken into consideration. ARToolkit is the product of AR community and it is registered under the GNU General Public License. The user is provided with basic source code that lets the user easily develop Augmented Reality applications. Despite the fact that AR is not a new technology, people may unaware or unfamiliar with its existence. Therefore this paper is intended to (1) give an overview of augmented reality; and provides (2) solution to the technical problems that one’s will face in setting up open-source augmented reality toolkit.